Excellence in agronomy partners survey — results report - Schuetz, Tonya; Ampadu-Boakye, T.; Calì, D. (2024)
Excellence in Agronomy (EiA) is a CGIAR Initiative that has embarked on a journey with many partners to deliver an increase in productivity and quality per unit of input (agronomic gain) for millions of smallholder farming households in prioritized farming systems by 2030. This Initiative places a strong emphasis on women and young farmers and aims to show a measurable impact on: Food and nutrition security | Income | Resource use | Soil health | Climate resilience | Climate change mitigation. This can only be achieved through and is being implemented in partnership with many different organizations.